Reinforcing experience of 18 students in Integrity and Anti-Corruption Course KIAR through visit to MACC Pahang - Hadijah, Ahmad (2023)
PEKAN, 7 December 2022 – Student visits to any Malaysian Anti-Corruption Commission (MACC) office have been outlined in the Student Learning Plan to reinforce the learning experience.